Adjunctive Garcinia mangostana Linn. (Mangosteen) Pericarp for Schizophrenia: A 24-Week Double-blind, Randomized, Placebo Controlled Efficacy Trial: Péricarpe d'appoint Garcinia mangostana Linn (mangoustan) pour la schizophrénie : un essai d'efficacité de 24 semaines, à double insu, randomisé et contrôlé par placebo. (April 2021) - Turner, Alyna; Baker, Andrea; Dean, Olivia M.; Walker, Adam J.; Dodd, Seetal; Cotton, Susan M.; Scott, James G.; Kavanagh, Bianca E.; Ashton, Melanie M.; Brown, Ellie; McGrath, John J.; Berk, Michael
Objectives: Garcinia mangostana Linn. ("mangosteen") pericarp contains bioactive compounds that may target biological pathways implicated in schizophrenia. We conducted a double-blind randomized placebo-controlled trial evaluating the efficacy of adjunctive mangosteen pericarp, compared to placebo, in the treatment of schizophrenia. Methods: People diagnosed with schizophrenia or schizoaffective disorder ( Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition ), recruited across 2 sites (Brisbane and Victoria, Australia), were randomized to receive 24 weeks of adjunctive mangosteen pericarp (1, 000 mg/day) or matched placebo. The primary outcome measure was the Positive and Negative Symptom Scale total score. Secondary outcomes included positive and negative symptoms, general psychopathology, clinical global severity and improvement, participant reported overall improvement, depressive symptoms, functioning, quality of life, and safety data at 24 and 28 weeks (4 weeks postdiscontinuation). Data were collected from July 2016 to February 2019. Results: Baseline assessments were conducted on 148 people (mangosteen = 74, placebo = 74); data analyses were conducted on 136 (92%) participants with postbaseline data. The treatment group had significantly higher symptom severity compared to placebo, and both groups significantly improved on all symptom, functioning, and quality of life measures over time. No between-group differences were found for the rate of change between baseline and 24 or 28 weeks. Conclusion: Despite promising preclinical and clinical work, our results do not support mangosteen pericarp extract as an adjunctive treatment for schizophrenia or schizoaffective disorder.